Volumetric extraction of pulmonary blood vessels from computerized tomography scans [Bilgisayarli tomografi görüntülerinden akciǧer kan damarlarinin volümetrik gösterimi] - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2018)
In this study we created 3D model of pulmonary blood vessels in order to help surgeons while they are performing bronoschopy which is for cancer detection on early stages and preventing unintended interception to blood vessels during process. From Computerized Tomography scans, masks are created by using morphological operations which are used to segment lungs and blood vessels. Segmented blood vessels then shown in 3D space by relation of their pixel intensities. © 2018 IEEE.
Keywords: Biomedical Image Processing; Blood Vessel Segmentation; Pattern Recognition; Pulmonary Computerized Tomography